2012
DOI: 10.1590/s1679-62252012000400003
|View full text |Cite
|
Sign up to set email alerts
|

Deficient downstream passage through fish ladders: the case of Peixe Angical Dam, Tocantins River, Brazil

Abstract: Downstream passage through fish ladders and other facilities remains largely uninvestigated in South America. In view of this concern, we monitored ascending and descending fish movements through the fish ladder at Peixe Angical Dam, upper Tocantins River, Brazil, between September 2009 and August 2010. To investigate the extent of downstream passage, the fish fauna was sampled monthly (i) at sites upstream and downstream from the dam and (ii) inside the ladder. To distinguish between ascending and descending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…), despite recent studies have shown that fish do not use ladders as a descending route (Agostinho et al . , ; Pelicice and Agostinho , ; Brito and Carvalho ). This inefficiency may be related to the low density of fish above the dam, which may be a consequence of the barrier imposed by the reservoir.…”
Section: The Reservoir As An Ecological Barriermentioning
confidence: 98%
See 2 more Smart Citations
“…), despite recent studies have shown that fish do not use ladders as a descending route (Agostinho et al . , ; Pelicice and Agostinho , ; Brito and Carvalho ). This inefficiency may be related to the low density of fish above the dam, which may be a consequence of the barrier imposed by the reservoir.…”
Section: The Reservoir As An Ecological Barriermentioning
confidence: 98%
“…, ; Esguicero and Arcifa ; Terra et al . ; Pelicice and Agostinho ; Petesse and Petrere ). The paucity of migratory species in reservoirs is a well‐recognized trend and has directly affected fisheries (Petrere et al .…”
Section: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Other relevant aspects that should be considered in discussions on fish passages are their high selectivity (Agostinho et al, 2007d), the difficulty in controlling which species go through the passage (Pompeu et al, 2012), and the absence of downstream movement of adults and their offspring (Agostinho et al, 2007c(Agostinho et al, , 2011Suzuki et al, 2011;Pelicice and Agostinho, 2012). Solutions to the existing bottlenecks concerning recommendations of fish passages as a tool to mitigate impacts on migratory species must address the following issues: (i) whether the passages are efficient to attract fish and to allow free movements; (ii) whether the reservoirs represent a barrier to downstream movement of adult fish or to the drift of their eggs and larvae (Agostinho et al, 2007c; in press), (iii) whether long-distance migratory species have distinct behaviors and the swimming ability to be attracted to and to overcome the water flow in a fish passage; (iv) whether the passage is safe, with low rates of injury or predation , (v) whether clear objectives exist (e.g.…”
Section: Management and Impact Mitigationmentioning
confidence: 99%
“…The Paranã and Cana Brava rivers, for example, may provide essential habitats because these tributaries are free flowing. The same is valid for the 230 km stretch between Peixe Angical dam and Lajeado reservoir, which contains large tributaries and small wetlands (Pelicice & Agostinho, 2012). Conservation efforts, therefore, must give high priority to the conservation of remnant lotic sites.…”
Section: Discussionmentioning
confidence: 90%